Feminism, democracy and culture - Eva Martínez Sempere (Feminismo/s, 2008)
Enlightened feminism has been the necessary condition for democracy, and, in turn, democracy is the only political system able to guarantee the equal human dignity of each person, and her or his equality of rights to develop her or his personality freely. This achievement, included in international and European Union legislation and in democratic constitutions, which requires the action of the public authorities to create conditions of equality, is currently threatened due to the resistance of the patriarchy under the guise of communitarian multiculturalism and its defence of the cultural identity of the group, thus sacrificing women and children. The existence of democratic pluralism through the common legal system of the state is the only guarantee for protecting every person, even against her or his family. For this reason, legal pluralism, which categorizes people according to gender, ethnic group or religion, cannot be accepted. We need to move from an authoritarian social model to a communal social model.